PERUBAHAN SOSIAL PADA TRADISI TURUN MANDI BAYI DI DESA KOTOBARU KECAMATAN SINGINGI HILIR KABUPATEN KUANTAN SINGINGI - Ria Febriana; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in the village of Singingi Hilir Subdistrict Kotobaru Singingi Kuantan. The purpose of this study is the first to know what kind of baby shower tradition in the village down Kotobaru. The second objective is to determine any changes that occur in a tradition passed down in the village Kotobaru baby shower. The third objective is to determine what are the factors that cause a change in the tradition of a baby shower down in the village Kotobaru. Analyzing the data in this study using the Qualitative Research Methods. Qualitative Research Methods This is an analysis that seeks to provide a detailed description based on statements obtained from the facts of the field and is also supported by the data-primary or secondary data to support the existing data. Qualitative research is presented in the form of words from the interview the author with the respondents that describe the specific circumstances of the people in the village Kotobaru on a tradition passed down baby showers, changes in the tradition passed down baby showers and the factors that cause a change in a tradition passed down baby shower Village Kotobaru. The results of this field study showed that the changes occurred in the tradition of bathing the baby in the village down Kotobaru even traditions that existed long ago began to fade. It is caused by several factors that influence the changes that occur in a tradition passed down baby shower that is the internal and external factors.Keywords: Baby Shower Fall Tradition, Change